Studies of Madagascan Ptiliidae (Coleoptera) 1: The Tribe Discheramocephalini including eighteen new species - Darby, Michael (Zootaxa, 2013)
This is the first report detailing Ptiliidae collected from forest leaf litter by the Moravian Museum expeditions to Madagascar 2010-2011.18 new species in three genera are described and figured: Discheramocephalus bisulcatus sp. n.; D. vasilii sp. n.; Cissidium banari sp. n.; Dacrysoma andasibense sp. n.; D. imitatum sp. n.; D. delicatum sp. n.; D. denticulatum sp. n.; D. dolorosum sp. n.; D. fabrum sp. n.; D. fusum sp. n.; D. longulum sp. n.; D. nigerrimum sp. n.; D. pilosum sp. n.; D. rahanitriniainae sp. n.; D. ranomafanense sp. n.; D. ravelosoni sp. n.; D. subinsulsum sp. n.; and D. varium sp. n..